Unusual causes of peritonitis in a peritoneal dialysis patient: Alcaligenes faecalis and Pantoea agglomerans - Arikan Hakki; Ari Elif; Tigen Elif; Asicioglu Ebru; Kahveci Arzu; Odabasi Zekaver; Ozener Cetin (BMC, 2011)
Abstract An 87 -year-old female who was undergoing peritoneal dialysis presented with peritonitis caused by Alcaligenes faecalis and Pantoea agglomerans in consecutive years. With the following report we discuss the importance of these unusual microorganisms in peritoneal dialysis patients.